Chile : Selected Issues Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The cornerstone of Chile's impressive fiscal performance and strong fiscal system has been its structural balance rule. It has helped to insulate public spending from copper price cycles and improve the government's net financial position. Chile should adopt a full-fledged medium-term fiscal framework to improve fiscal planning and provide a framework for addressing temporary deviations from the fiscal rule. Publishing additional fiscal indicators in the budget, such as the non-copper structural balance, could provide more comprehensive information on the impact of fiscal policy on the domestic demand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet